1999
DOI: 10.1099/00222615-48-2-205
|View full text |Cite
|
Sign up to set email alerts
|

Clonal structure of Providencia alcalifaciens strains isolated from diarrhoeal stools in Sāo Paulo, Brazil

Abstract: Clonal analysis based on ribotyping demonstrated that Providencia alcalifaciens strains isolated mainly from diarrhoeal stools in SQo Paulo, Brazil, were clustered into two main groups. Eleven distinct ribotype patterns were identified with CluI, EcoRV and MluI restriction endonucleases. I! alculifaciens strains with invasive properties were of two ribotype patterns that differed from those identified among non-invasive strains. The ribotyping results confirmed that I! ulcalifaciens strains associated with dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
1
4
0
1
Order By: Relevance
“…A British survey of travelers to Mediterranean countries between 1987 and 1988 found a significant association between the recovery of P. alcalifaciens and diarrheal disease (237). These initial findings have been subsequently supported by other studies describing individual cases of P. alcalifaciens-associated diarrhea and at least three outbreaks of gastrointestinal disease, including one large outbreak involving Ͼ270 children in Japan (238)(239)(240). P. alcalifaciens strains implicated in diarrheal disease are invasive in HEp-2 cell monolayers, although the type of diarrhea that they produce is secretory (239, 241); some strains additionally produce a cytolethal distending toxin (242).…”
Section: Emerging Enteropathogenssupporting
confidence: 64%
See 1 more Smart Citation
“…A British survey of travelers to Mediterranean countries between 1987 and 1988 found a significant association between the recovery of P. alcalifaciens and diarrheal disease (237). These initial findings have been subsequently supported by other studies describing individual cases of P. alcalifaciens-associated diarrhea and at least three outbreaks of gastrointestinal disease, including one large outbreak involving Ͼ270 children in Japan (238)(239)(240). P. alcalifaciens strains implicated in diarrheal disease are invasive in HEp-2 cell monolayers, although the type of diarrhea that they produce is secretory (239, 241); some strains additionally produce a cytolethal distending toxin (242).…”
Section: Emerging Enteropathogenssupporting
confidence: 64%
“…Most isolates of P. alcalifaciens recovered from diarrheal stools have been isolated in pure culture, as predominant flora, or without any other recognizable enteropathogens being detected (237,240,243). A selective medium, termed PAM (Providencia alcalifaciens medium), has been described for the recovery of this species from feces (244).…”
Section: Emerging Enteropathogensmentioning
confidence: 99%
“…A presença de P. alcalifaciens em 31,25% dos monoblocos chama a atenção pelo fato de tal microrganismo ser reconhecidamente causador de gastroenterite com temida virulência [9,14]. Já a K. pneumoniae, identificada em 18,75% das caixas, tem sido isolada de alimentos marinhos por ser um habitante natural da água.…”
Section: -Resultados E Discussãounclassified
“…However, there were also non-invasive isolates in those groups. In a recent study, Guth et al [9] showed that invasive and non-invasive isolates had different ribotypes. P. alcalifaciens isolates with invasive properties belonged to two ribotype patterns that differed from those identi®ed among non-invasive isolates, suggesting that the invasive and the non-invasive isolates were derived from different clones.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent clonal analysis studies showed that isolates with invasive properties represented speci®c clones, which differed from the non-invasive ones [9].…”
Section: Introductionmentioning
confidence: 99%